Strength and power training improve skill performance in volleyball players - Kátia Kitamura; Hamilton Roschel; Irineu Loturco; Leonardo Lamas; Valmor Tricoli; Paulo Vicente João; Gilbert Fellingham; Carlos Ugrinowitsch
Abstract Aim: This study aimed to test the influence of functional improvements in volleyball skills performance. Methods: Twenty-eight amateur female volleyball players were assigned to Skill (S: n = 14, 19.5 ± 4.6 yrs; 169.7 ± 7.2 cm; 62.9 ± 12.7 kg) or Skill and Strength/Power (S+SP: n = 14; 18.6 ± 3.5 yrs; 169.7 ± 5.1 cm; 63.3 ± 9.2 kg). S+SP performed eight weeks of volleyball and conditioning training. S maintained only volleyball training. Functional variables (i.e. strength, power, and agility measures) and volleyball skills performance in a game-situation context were assessed before and after training. Results: 1-RM squat and bench press, time at modified agility T-test, peak power at bench throw and medicine-ball throw distance improved for the S+SP (p<0,05). S group increased only in medicine-ball throw distance (p<0.05). There were no differences between groups in the functional variables tested (p>0.05). The probabilities of a perfect set and an attack 'kill' in S+SP improved (¶>0.90). Changes from pre to post-training were higher in S+SP than in S for a perfect set, 'stuff block' and defense with displacement (¶>0.90). Conclusion: Our data suggest that functional improvements may positively affect volleyball skills performance. Although functional variables revealed only within-group changes, S+SP produced greater improvements in skill performance than S, supporting the use of conditioning training to improve volleyball performance.